2020
DOI: 10.1093/ajcp/aqaa073
|View full text |Cite
|
Sign up to set email alerts
|

Scoring of Programmed Death-Ligand 1 Immunohistochemistry on Cytology Cell Block Specimens in Non–Small Cell Lung Carcinoma

Abstract: Objectives Recent investigations have shown strong correlations between cytology and surgical non–small cell lung carcinoma (NSCLC) specimens in programmed death-ligand 1 (PD-L1) immunohistochemical (IHC) evaluations. Our study aims to evaluate the reproducibility of PD-L1 IHC scoring in NSCLC cytology cell blocks (CBs) and to assess the impact of CB cellularity, method of sample collection, and observer subspecialty on scoring agreement. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Studies analyzing PD‐L1 testing on lung carcinoma cytology specimens originated mostly from the USA, followed by publications arising from Italy, Canada, United Kingdom, China, Germany, Japan, India, Turkey and other countries. The Dako clone 22C3 was the most common clone analyzed on cytology specimens, followed by the Ventana SP263 clone 17–67 . The data collected included the clone type used in each study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies analyzing PD‐L1 testing on lung carcinoma cytology specimens originated mostly from the USA, followed by publications arising from Italy, Canada, United Kingdom, China, Germany, Japan, India, Turkey and other countries. The Dako clone 22C3 was the most common clone analyzed on cytology specimens, followed by the Ventana SP263 clone 17–67 . The data collected included the clone type used in each study.…”
Section: Resultsmentioning
confidence: 99%
“…Gosney et al's systematic review 105 analysed studies that compared PD-L1 scores on cytological CBs with histology; they showed good concordance using tumour cell expression cutoffs of ≥1% and ≥50%, provided 100 tumour cells are present. 106 Nevertheless, false negatives may occur with cytology samples due to low numbers of tumour cells and PD-L1 heterogeneity within tumours. Cytological samples are not suitable for PD-L1 assays using the SP142 antibody clone which includes a count of positive tumour infiltrating immune cells, due to the lack of tissue context and inability to determine if immune cells are tumour-related.…”
Section: Pd-l1mentioning
confidence: 99%
“…Degenerate tumour cells may show loss of cell membrane integrity and display spurious cytoplasmic staining. Hernandez et al 106 found that correlation with histology was better when pathologists with pulmonary expertise assessed the samples.…”
Section: Biomarker Immunocytochemistrymentioning
confidence: 99%
“…To maintain high accuracy, it is important to adhere to the minimum adequacy requirement of 100 viable tumour cells, 54 to rigorously validate new PD-L1 protocols on cytology specimens, and to train the cytopathologists. 34,55 Most studies on PD-L1 expression in cytology material have used cell blocks 48,[56][57][58][59] or direct smears. 60,61 Though few clinical trials thus far use cytology samples, several studies show that PD-L1 can be assessed on cell blocks and smears with high interobserver agreement and agreement with surgical samples (Figure 3).…”
Section: Predictivetestingforimmunotherapymentioning
confidence: 99%